Health and fitness study of Semarang soccer players: the role of VO2 max, body mass index, age and length of training - Didi Yudha Pranata; M. Furqon Hidayatullah; Sulaiman Sulaiman; Sri Sumartiningsih; Harry Pramono; Heny Setyawati (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Physiological factors influence the performance of football players, so a coach must know and analyze these factors. This study explored the relationship between Body Mass Index (BMI) and maximal aerobic capacity (VO2 max) on the health and fitness of soccer players in Semarang. The study involved 41 soccer players from various local clubs, aged 14-16 years, who were evaluated through BMI measurement by measuring height and weight and VO2 max test with Multi-Stage Fitness Test. Data were analyzed using Pearson correlation to identify the strength and direction of the relationship between variables. The analysis results showed that: 1) Age had a moderate positive correlation with VO2 max (r = 0.366, p = 0.018), indicating that VO2 max values tend to increase with age. However, age showed no significant correlation with the other variables (BMI criteria, BMI, and length of training), 2) BMI criteria had a very high and significant correlation with BMI (r = 0.785, p < 0.001), confirming that the BMI criteria used were highly correlated with actual BMI values. However, no significant correlation was found between BMI criteria and VO2 max and training duration, 3) BMI showed no significant correlation with VO2 max (r = 0.191, p = 0.232) nor with training duration (r = 0.088, p = 0.585), 4) VO2 max had a moderate and significant positive correlation with training duration (r = 0.639, p < 0.001), suggesting that individuals with longer training duration tend to have higher VO2 Max. This study concludes that there is a significant relationship between age and VO2 max as well as between training duration and VO2 max, indicating the importance of both factors in aerobic capacity improvement programs. In addition, the BMI criteria used proved to be valid in reflecting actual BMI values. These results underscore the importance of considering age and duration of training in football players' fitness programs as well as the validity of the BMI criteria used in the study.